2020
DOI: 10.3389/fphar.2020.00737
|View full text |Cite
|
Sign up to set email alerts
|

CCT020312 Inhibits Triple-Negative Breast Cancer Through PERK Pathway-Mediated G1 Phase Cell Cycle Arrest and Apoptosis

Abstract: Triple-negative breast cancer (TNBC) has a poor prognosis due to the lack of specific therapeutic targets. CCT020312, a selective eukaryotic translation initiation factor 2 alpha (eIF2a)/protein kinase RNA-like endoplasmic reticulum kinase (PERK) activator, may have a potent anti-tumor effect. In the present study, we examined the effects of CCT020312 on TNBC and explored the underlying mechanism. We found that CCT020312 inhibited the viability of TNBC cell lines, MDA-MB-453 and CAL-148, by inducing apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…The compound CCT020312 was found in a phenotypic screen that assayed for G1/S checkpoint activators in human colon carcinoma cells [190]. It also inhibited triple-negative breast cancer by G1 phase cell cycle arrest [191]. CCT020312 showed neuroprotection in cellular and mouse models of tauopathies, reducing tau phosphorylation in P301S tau mice and significantly improving their memory and motor function, with a reduction in motoneuron loss [129].…”
Section: Perk Pathway Activationmentioning
confidence: 99%
“…The compound CCT020312 was found in a phenotypic screen that assayed for G1/S checkpoint activators in human colon carcinoma cells [190]. It also inhibited triple-negative breast cancer by G1 phase cell cycle arrest [191]. CCT020312 showed neuroprotection in cellular and mouse models of tauopathies, reducing tau phosphorylation in P301S tau mice and significantly improving their memory and motor function, with a reduction in motoneuron loss [129].…”
Section: Perk Pathway Activationmentioning
confidence: 99%
“…The top 10 significant KEGG pathways derived from GSEA among the three datasets showed only two common pathways, cell cycle and glycosphingolipid biosynthesis lacto/neolacto series (Figure 4C). Discovery of the cell cycle pathway validates our approach as cell cycle deregulation is known in TNBC, and cell cycle-targeting drugs have shown promise in clinical trials [35]. Focusing on glycosylation pathways that were enriched in all three datasets, regardless of ranking, we identified three more pathways: glycosylphosphatidylinositol (GPI)-anchor biosynthesis, which was down-regulated in TNBC, and two pathways in glycosaminoglycan biosynthesis which were up-regulated in TNBC (Figure 4D).…”
Section: Candidate Discoverymentioning
confidence: 61%
“…Some studies have reported that the activation of ER stress signaling pathway IRE1-XBP1s induces cell cycle arrest by increasing expressions of p21 and p27 ( 7 ). The activation of PERK/eIF2α signaling has been shown to cause loss of cyclin D1, resulting in G1 cell cycle arrest ( 6 , 47 ). However, the current study does not demonstrate a direct association of activation of ATF6 signaling pathway with cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%